Inklinasi Optimal Panel Surya Sumbu Tetap di Indonesia - Priyatikanto, Rhorom (Institut Teknologi Bandung, 2016)
Indonesia possesses a significant potential solar energy. According to in-situ measurements, solar irradiation overwestern part of Indonesia is about 4.5 kWh/m2, while the higher value of 5.1 kWh/m2 is obtained at the easternpart. Installation of fixed-axis solar panel oriented to certain optimum inclination becomes an effective way togather the solar energy. Optimum inclination angle for every location needs to be determined by considering thegeographical latitude, topography and local climate. In this work, the optimum inclination angle of fixed axis solarpanel is calculated by employing ESRA (European Solar Radiation Atlas) model that invokes cloud cover maps fromfive-years visual observation of MTSAT Himawari 6 and Himawari 7 from 2008 to 2012. Topographical map fromUSGS-EROS Data Center and Linke turbidity maps from SoDa (Solar Radiation Data) are used for the calculation.The result is optimum inclination map for Indonesia with medium resolution of 0.25º × 0.25º. The optimum valuesdo not only depend on the latitude of the location but also the variation of the weather, especially cloud cover overthe year. It is found that the optimum inclinations deviate from the latitude by small angle between -1º in the northeast parts of Indonesia and 2º in the south west regions. This pattern is in agreement with the spatial variation ofprecipitation in Indonesia as reported by researchers in the past.